2022
DOI: 10.1080/22221751.2022.2071172
|View full text |Cite
|
Sign up to set email alerts
|

Solely HBsAg intrauterine exposure accelerates HBV clearance by promoting HBs-specific immune response in the mouse pups

Abstract: Chronic hepatitis B virus (HBV) infection due to perinatal mother-to-infant transmission (MTIT) remains a serious global public health problem. It has been shown that intrauterine exposure to HBV antigens might account for the MTIT-related chronic infection. However, whether hepatitis B surface antigen (HBsAg) intrauterine exposure affected the offspring’s immune response against HBV and MTIT of HBV has not been fully clarified. In this study, we investigated the effects and the potential mechanisms of the HBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Through the research on a mouse model of only HBsAg exposure in utero , Ning et al. came to the first conclusion that, contrary to what others had previously thought, HBeAg played an immunosuppressive effect on the offspring; only HBsAg exposure in utero did not develop the immune tolerance to HBV on the fetus; however, when re-exposed to HBV, the offspring could speed up the elimination of HBV in the body; and this beneficial effect may be related to only HBsAg exposure in utero , which could activate antigen-presenting dendritic cells and then induce an increase of the HB-specific CD8 + T cells and secretion of interferon (IFN)-γ in the hepar of mice ( 62 ). Another research by cord blood analysis also showed that immunity of newborn infants can be beneficially affected due to the HBV-infected state of their Asian mothers; it was mainly manifested as the enhancement of innate immune cell maturation and the increasement of Th1 development, and specially showed that low levels of IL-10 (Th2-related cytokines) and high levels of IL-12p40, IFN-α2 (Th1-related cytokines); importantly, such enhancement effect led to the robust response of the neonatal immune cells when they were exposed in vitro to pathogens that were unrelated to their condition, and the pathogens were Pseudomonas aeruginosa , Salmonella typhimurium , uropathogenic, Escherichia coli , Acinetobacter baumanii , and Listeria monocytogenes ; however, this beneficial effect cannot be demonstrated in the baby Caucasian HBV-infected mother’s delivery, which was explained by different HBV genotypes; patients of Asian descent had HBV genotypes B/C, while patients of Caucasian descent had HBV genotype D ( 63 ).…”
Section: T Cells and Hbv Infectionmentioning
confidence: 99%
“…Through the research on a mouse model of only HBsAg exposure in utero , Ning et al. came to the first conclusion that, contrary to what others had previously thought, HBeAg played an immunosuppressive effect on the offspring; only HBsAg exposure in utero did not develop the immune tolerance to HBV on the fetus; however, when re-exposed to HBV, the offspring could speed up the elimination of HBV in the body; and this beneficial effect may be related to only HBsAg exposure in utero , which could activate antigen-presenting dendritic cells and then induce an increase of the HB-specific CD8 + T cells and secretion of interferon (IFN)-γ in the hepar of mice ( 62 ). Another research by cord blood analysis also showed that immunity of newborn infants can be beneficially affected due to the HBV-infected state of their Asian mothers; it was mainly manifested as the enhancement of innate immune cell maturation and the increasement of Th1 development, and specially showed that low levels of IL-10 (Th2-related cytokines) and high levels of IL-12p40, IFN-α2 (Th1-related cytokines); importantly, such enhancement effect led to the robust response of the neonatal immune cells when they were exposed in vitro to pathogens that were unrelated to their condition, and the pathogens were Pseudomonas aeruginosa , Salmonella typhimurium , uropathogenic, Escherichia coli , Acinetobacter baumanii , and Listeria monocytogenes ; however, this beneficial effect cannot be demonstrated in the baby Caucasian HBV-infected mother’s delivery, which was explained by different HBV genotypes; patients of Asian descent had HBV genotypes B/C, while patients of Caucasian descent had HBV genotype D ( 63 ).…”
Section: T Cells and Hbv Infectionmentioning
confidence: 99%